2003
DOI: 10.5194/acp-3-863-2003
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on "Homogeneous nucleation of NAD and NAT in liquid stratospheric aerosols: insufficient to explain denitrification" by Knopf et al.

Abstract: Abstract. In a recent published paper Knopf et a1. (2002) have suggested that the homogeneous freezing behavior of stratospheric aerosols, under polar winter conditions, can be simulated experimentally in large bulk phase-sized droplet samples (0.12-0.27 cm in diameter). Their hypothesis is based on the fact that a nucleus, which freezes the supercooled phase, forms within the bulk volume of a given sample, and therefore, if large bulk volumes don't freeze in the laboratory, then small volumes in particles mos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
(10 reference statements)
0
17
1
Order By: Relevance
“…A reduction in the surface nucleation rates by a factor between 20 and 10 corresponds to an increase of ≈4% or ≈1 kcal mol −1 in the free energy ( G) of formation of a crystal nucleus on the droplet surface, applying the parameterization of G by Tabazadeh et al (2002). As mentioned by the authors, the empirical parameterizations of G are based on laboratory nucleation experiments on concentrated, pure aqueous nitric acid, extrapolated to stratospheric conditions with much more dilute solutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A reduction in the surface nucleation rates by a factor between 20 and 10 corresponds to an increase of ≈4% or ≈1 kcal mol −1 in the free energy ( G) of formation of a crystal nucleus on the droplet surface, applying the parameterization of G by Tabazadeh et al (2002). As mentioned by the authors, the empirical parameterizations of G are based on laboratory nucleation experiments on concentrated, pure aqueous nitric acid, extrapolated to stratospheric conditions with much more dilute solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming these hydrate particles form by homogeneous nucleation would require production rates orders of magnitude higher than derived from laboratory experiments (Knopf et al, 2002). We have applied the surface nucleation mechanism of Tabazadeh et al (2002) because this, to our knowledge, is the latest published available parameterisation of hydrate nucleation out of STS working at temperature above the ice frost point. Secondly, the surface nucleation seems more consistent with laboratory experiments (Tabazadeh et al, 2002), compared to a corresponding volume nucleation parameterisation (Tabazadeh et al, 2001;Salcedo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knopf et al (2002) have also shown that the linear extrapolation of laboratory data to stratospheric conditions by Tabazadeh et al (2001) gave physically unrealistic results under some conditions, and was likely to overestimate freezing rates. The general applicability of laboratory-measured homogeneous nucleation rates to the stratosphere has been called into question because of the potential role of surface contaminants (Tabazadeh et al, 2003). At present, the possibility of homogeneous nucleation of nitric acid hydrates remains an open and poorly quantified issue.…”
Section: Introductionmentioning
confidence: 99%